2005
DOI: 10.1098/rspb.2004.2896
|View full text |Cite
|
Sign up to set email alerts
|

Voluntarily controlled bi–stable slant perception of real and photographed surfaces

Abstract: We have quantified voluntarily selected perceived slant of real trapezoidal surfaces (a 'reverse-perspective' scene) and their photographed counterparts (pictorial space). The surfaces were slanted about the vertical axis and observers estimated slant relative to the frontal plane. We were particularly interested in those cases in which binocular disparity and monocular perspective provided conflicting slant information. We varied the monocularly and binocularly specified surface slants independently across st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…Moreover, two alternating slants were perceived when perspective-and disparity-specified quite different slants. Our results are similar to those reported previously for slants about a vertical axis (van Ee et al, 2003;van Ee et al, 2002;van Ee et al, 2005b). In experiment 2 we investigated gaze positions while subjects viewed the stimulus and found that eye movements were not essential for the instigation of a perceptual flip, which means that perceptual flips were governed by a cognitive process.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, two alternating slants were perceived when perspective-and disparity-specified quite different slants. Our results are similar to those reported previously for slants about a vertical axis (van Ee et al, 2003;van Ee et al, 2002;van Ee et al, 2005b). In experiment 2 we investigated gaze positions while subjects viewed the stimulus and found that eye movements were not essential for the instigation of a perceptual flip, which means that perceptual flips were governed by a cognitive process.…”
Section: Discussionsupporting
confidence: 91%
“…The perceived slants about the horizontal axis are similar to those found previously for slants about the vertical axis (van Ee, Adams, & Mamassian, 2003;van Ee et al, 2002;van Ee, Krumina, Pont, & van der Ven, 2005b). In other words the perceived slants can be understood in a Bayesian frame work that describes the quantitative aspects of perceived slant on the basis of the likelihoods of both perspective and disparity slant information combined with prior assumptions about the shape and orientation of objects in the scene (van Ee et al, 2003).…”
Section: Resultssupporting
confidence: 78%
“…Recently, Erkelens (2013a) conducted a comprehensive study with both opposite-and same-signed slants specified by disparity and perspective cues and provided evidence that binocular disparity played no role in determining the final percept. However, most of these studies dealt with either (a) quantitative assessments (magnitude of slant or depth) using computerdisplayed stimuli (Allison and Howard, 2000;Dosher et al, 1986;Erkelens, 2013aErkelens, , 2013bSato & Howard, 2001;van der Meer, 1979;van Ee et al, 2002van Ee et al, , 2003 or (b) qualitative scene layout perception using physical 3-D stimuli (Cook et al, 2002;Keane, Silverstein, Wang, & Papathomas, 2013;Papathomas, 2002;Papathomas, Baker, Yeshua, Zhuang, & Ng, 2012;Rogers & Gyani, 2010;Sherman, Papathomas, Jain, & Keane, 2011;van Ee, Krumina, Pont, & van der Ven, 2005). To our knowledge, only van Ee et al (2005) studied quantitative aspects of slant using physical planar stimuli.…”
Section: Introductionmentioning
confidence: 99%